Die asymptotische Entwicklung für den Dichtefunktionen - Survila, P. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:П. Сурвила. Асимптотические разложения для плотностейP. Survila. Tankių asimptotiniai išdėstymai